2024
DOI: 10.3390/ani14030373
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant and Hepatoprotective Potential of Berberine and Silymarin on Acetaminophen Induced Toxicity in Cyprinus carpio L.

Lăcrămioara Grădinariu,
Lorena Dediu,
Mirela Crețu
et al.

Abstract: Berberine (BBR) and silymarin (SM) are natural compounds extracted from plants known for their antioxidant and chemoprotective effects on the liver. The present study aimed to investigate the beneficial properties of BBR and SM and the association of BBR with SM on liver function using fish as “in vivo” models. Moreover, the study investigated their hepatoprotective role after acetaminophen (APAP) exposure. For this purpose, the fish (N = 360; 118.4 ± 11.09 g) were fed with control or experimental diets for 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…Berberine, the specific isoquinoline alkaloid mainly extracted from common barberry root and stem barks, is formulated for oral administration alone or in various combinations. The administration of berberine-based phytotherapeutics could have a beneficial impact on lipid and carbohydrate metabolism, particularly on glucose homeostasis, being helpful in weight loss, diabetes mellitus [4] and endocrine disorders, liver diseases [5], cardiovascular diseases, atherosclerosis, neurodegenerative diseases, rheumatic diseases, and infectious diseases [1]. Several studies reported berberine-induced toxicity in humans and mice [1].…”
Section: Introductionmentioning
confidence: 99%
“…Berberine, the specific isoquinoline alkaloid mainly extracted from common barberry root and stem barks, is formulated for oral administration alone or in various combinations. The administration of berberine-based phytotherapeutics could have a beneficial impact on lipid and carbohydrate metabolism, particularly on glucose homeostasis, being helpful in weight loss, diabetes mellitus [4] and endocrine disorders, liver diseases [5], cardiovascular diseases, atherosclerosis, neurodegenerative diseases, rheumatic diseases, and infectious diseases [1]. Several studies reported berberine-induced toxicity in humans and mice [1].…”
Section: Introductionmentioning
confidence: 99%